Mapping the Contours of an Imperial and Domestic Settler Subjectivity: Hylda Richards and the Heteroglossia of her Epoch - Ngoshi, Hazel T. (Unisa Press, 2016)
Bakhtinian dialogism places great emphasis on situating texts within the dialogues of their historical contexts. this article deploys Bakhtin's concept of heteroglossia to identify ideological and discursive currents/voices running through Hylda Richards' Next Year Will be Better, an autobiographical account. The context in which these currents are discussed is the construction of autobiographical subjectivity. This article argues that Richards' subjectivity is constituted against the background of a historical epoch populated with the heteroglossia of imperial and colonial societies. The subjectivities that emerge in this context are those of pioneer and domestic settler subjects. In addition, the article maps the relationship between Richards' narrative to the languages of her epoch and how she articulates these. The discussion establishes that her utterances in the narrative are polemical and largely inspired by pre-existing scripts about the condition of Africa and the moral superiority of white people, especially the English race. The article foregrounds Bakhtin's insistence on the impossibility of forming self-identities outside dialogue, whether subjects are conscious of the dialogising words or not.